Penerapan Garuda Smart City Model dalam Menganalisa Kesiapan Pemerintah Kabupaten Tulang Bawang Barat Dalam Membangun Konsep Smart City - Bhianta Wijaya; Edi Surya Negara (CogITo Smart Journal, 2022)
West Tulang Bawang Regency was formed on March 20, 1997 through Law Number 2 of 1997 with an area of ​​1,201 Km2 or 22% of the area of ​​Lampung province. With such an area, of course, Tulang Bawang Barat district has many complex urban problems, especially for improving services to its people. Until 2019, through the MoU between the local government and the Banyuwangi Regency Government in the development of e-government, it was indicated that the West Tulang Bawang Regency Government had begun to be serious about dealing with regional problems using Information Technology assistance. By realizing the magnitude of the challenges and efforts to accelerate development and shorten the span of control of public services in the Sai Bumi Nengah Nyapur area. In line with these problems, the government of West Tulang Bawang Regency and other stakeholders are committed to accelerating the development of smart cities in West Tulang Bawang Regency. In order to produce a smart city that suits the needs of society and government. On this basis, researchers are trying to examine the readiness of Tulang Bawang Barat Regency in implementing the smart city concept by utilizing the measurement concept of the Garuda Smart City Model (GSCM) where this framework is commonly used in measuring the maturity of a city in implementing smart cities with the target of determining existing conditions, development of recommendations, roadmaps and ratings